PENERAPAN KOMBINASI MODEL PEMBELAJARAN KOOPERATIF TIPE MIND MAPPING DENGAN MAKE A MATCH UNTUK MENINGKATKAN KEAKTIFAN SISWA PADA MATA PELAJARAN KEARSIPAN - -, Nur Rahmi Akbarini - (Prosiding Seminar Pendidikan Ekonomi dan Bisnis, 2017)
ABSTRACTÂ The objective of this research is to improve the activeness in Archive subject matter of the students in Grade X of Office Administration of State Vocational High School 3 of Surakarta through the application of combination of the cooperative learning model between the mind mapping type and the make a match type. The type of researchÂ  conducted by the researchers is the Classroom Action Research (CAR). The subjects of researchÂ  were 32 students grade X department of office administration of State Vocational HighÂ  School 3 of Surakarta. The data sources of research were the subject matter teacher and the students. Techniques of data collected trought observation, documentation andinterview method. The data were analyzed by using the descriptive comparative technique and critical analysis technique. The result of research shows that the application of combination of the cooperative learning model between the mind mapping type and the make a match typecan improve the studentâs activeness in archive subject matter as much as 53.75%. Prior to the treatment the studentâs activeness is 31.26%. Following the treatment, it becomes 55.01% in Cycle I and 85.01% in Cycle II. In addition, the percentage of each aspect of the studentsâ activeness also improves as much as 50%. Prior to the treatment, the percentage of the visual aspect activities is 34.38%. Following the treatment, it becomes 56.26%in Cycle I and 84.38%in Cycle II. The percentage of the oral aspect activities improves as much as 59.37%. Prior to the treatment, the percentage of the oral aspect activities is 2.88%. Following the treatment, it becomes 46.88% in Cycle I and 81.25% in Cycle II. The percentage of the drawing aspect activities improves as much as 87.51%. Prior to the treatment, the percentage of the drawing aspect activities is 0%. Following the treatment, it becomes 53.13%in Cycle I and 87.51%in Cycle 2. The percentage of the mental aspect activities improves as much as 56.26%. Prior to the treatment, the percentage of the mental aspect activities is 31.25%. Following the treatment, it becomes 59.38% in Cycle I and 87.51% in Cycle II. The percentage of the emotional aspect activities improves as much as 46.87%. Prior to the treatment, the percentage of the emotional aspect activities is 37.51%. Following the treatment, it becomes 59.83% in Cycle I and 84.38%in Cycle II.Â Keywords : Mind mapping, Make a match, and Â Student ActivenessÂ ABSTRAKÂ Tujuan penelitian ini adalah untuk meningkatkan keaktifan siswa pada mata pelajaran Kearsipan Kelas X Administrasi Perkantoran 1 SMK Â Negeri 3 Surakarta melalui penerapan kombinasi model pembelajaran kooperatif tipe mind mapping dengan make a match. Penelitian ini merupakan penelitian tindakan kelas (PTK). Subjek penelitian adalah siswa kelas X Administrasi Perkantoran 1 SMK Negeri 3 Surakarta yang berjumlah 32 siswa. Sumber data berasal dari guru dan siswa. Teknik pengumpulan data adalah dengan observasi, wawancara, dan analisis dokumen.Analisis data menggunakan teknik deskriptif komparatif dan teknik analisis kritis. Hasil penelitian menunjukkan bahwa melalui penerapan kombinasi model pembelajaran kooperatif tipe mind mapping dengan make a match dapat meningkatkan keaktifan siswa sebesar 53,75% dari 31,26% pada pra siklus, 55,01% pada siklus 1, dan 85,01% pada siklus 2. Presentase dari masing-masing aspek keaktifan juga mengalami peningkatan. Aspek visual activities meningkat sebesar 50% dari 34,38% pada pra siklus, 56,26% pada siklus 1, dan 84,38% pada siklus 2.Aspek oral activities meningkat sebesar 59,37% dari 21,88% pada pra siklus, 46,88% pada siklus 1, dan 81,25% pada siklus 2. Aspek drawing activities meningkat sebesar 87,51% dari 0% pada pra siklus, 53,13% pada siklus 1, dan 87,51% pada siklus 2. Aspek mental activities meningkat sebesar 56,26% dari 31,25% pada pra siklus, 59,38% pada siklus 1, dan 87,51 pada siklus 2. Aspek emotional activities meningkat sebesar 46,87% dari 37,51 pada pra siklus, 59,83 pada siklus 1, dan 84,38% pada siklus 2.Â Kata Kunci: Mind Mapping, Make a Match, dan Keaktifan Siswa